EVALUATION OF WEED MANAGEMENT PRACTICES OF UPLAND RICE IN SOURTHERN GUINEA SAVANNA AREA OF NIGERIA (Federal University Gusau Faculty of Education Journal, 2025)
Field experiment was conducted on a farmer’s field in 2024 rainy seasons at Badeggi, Nigeria to study the comparative effects of different weed management on growth and yield performance of upland rice in the Sourthern guinea savanna. The treatments consisted of four early maturing upland rice varieties (NERICA 1, 2, 4, 7) and four weed management practices. The parameters measured were plant heigh t(cm), number of tillers and grain yield (kg ha-1). Treatment means were separated using the least significant difference (LSD) at P≤ 0.05. The result on plant height at 9 WAS indicated that NERICA 4 produced the tallest plants while the application of PE Butachior + POE Orizoplus gave the tallest plant at 9 WAS. Result of number of tillers (m2) indicated that at harvest the variety NERICA 4 produced the highest number of tillers (m2) among the other rice varieties. The result on grain yield (kg ha-1) among the varieties indicated that NERICA 7 had the highest grain yield of 1534.7 kg ha-1while on weed management the application of PE Butachlor + POE Orizo plus gave the highest grain yield of 1373.49 kg ha-1while weedy check gave the lowest yield of 1178.1 kg ha-1. Based on this study, it is concluded, that the application of PE Butachlor + POE Orizoplus produced the highest grain yield. It is recommended that farmers in this agro-ecological zone of Nigeria should adopt the variety NERICA 1 and the application of PE Butachlor + POE Orizoplus for suppressed weed growth and development, enhanced growth, and yield of upland rice.